Investigating the causal association of postpartum depression with cerebrovascular diseases and cognitive impairment: a Mendelian randomization study - Li, Jia; Li, Jinqiu; Shen, Lan; Wang, Huan; Zheng, Tian; Hui, Ying; Li, Xiaoxuan (Frontiers in Psychiatry, 2023)
Background Postpartum depression (PPD) is considered the most widespread puerperium complication. The associations of major depressive disorder with certain types of cerebrovascular diseases and cognitive function have been proposed, but the potential causal effects of PPD on these phenotypes are still unknown. Methods A Mendelian randomization (MR) research design with various methods (e.g., inverse-variance weighted method and MR pleiotropy residual sum and outlier test) was adopted to establish a causal relationship between PPD with cerebrovascular diseases and cognitive impairment. Results No causal relationship between PPD with carotid intima media thickness and cerebrovascular diseases (i.e., stroke, ischemic stroke, and cerebral aneurysm) was found. However, MR analyses indicated a causal association between PPD and decreased cognitive function (P = 3.55 × 10−3), which remained significant even after multiple comparison corrections using the Bonferroni method. Sensitivity analyses using weighted median and MR-Egger methods indicated a consistent direction of the association. Conclusion The causal association between PPD and cognitive impairment indicates that cognitive impairment is a critical aspect of PPD and thus cannot be regarded as an epiphenomenon. Addressing cognitive impairment and lessening the symptoms associated with PPD independently play significant roles in the treatment of PPD.